Dual Empire of Penal System - Tanaem, Jerymia Seky; Al-Uyun, Dhia; Aprilianda, Nurini (Indonesian Journal of Law and Society, 2024)
This study aimed to determine and analyze the "Ratio Decidendi" of Military judges at the Surabaya High Military Court III in deciding case Number 5K /PMT.III/AD/I/2022 against perpetrators of budget abuse by Military officials. The research method used by the author is a normative legal research method, by conducting research synchronization, systematics, and legal comparisons. The writer uses this type of normative legal research because, in formulating the problem, the writer emphasizes ratio decidendi to Military court decisions for misuse of budget management. This was influenced by the fact that Military Defendants who committed acts of misusing billions of rupiah in the budget were only sentenced to "Abuse of Power,” which refers to the Indonesian Military Code, with three months and twenty days in prison. In contrast to the main element, every person benefits himself and others or a corporation by abusing his authority, opportunities, or facilities available to him because this position or position can harm the country's finances and economy. Law No. 31/1999 Jo Law No. 20/2001 concerning the Eradication of Corruption Crimes should be a reference and basis for applying sanctions for criminal acts of corruption within the Military, not only referring to the provisions in the Army's Criminal Code. Keywords: Military Court, Military Penal Code, Corruption, Corruption Court, The Corruption Eradication Commission